Direct Synthesis of Sulfonimidoyl Guanidines from Sulfonimidoyl Azides under Dual (Cobalt and Photoredox) Catalysis. Issue 6 (15th February 2022) - Ravindra, S.; Nayak, Abinash; Irfana Jesin, C. P.; Chandra Nandi, Ganesh
Abstract: A visible‐light (456 nm) promoted dual catalytic (cobalt‐/photoredox) method for the direct synthesis of sulfonimidoyl guanidine via three‐component reaction of aryl amine, isonitrile and sulfonimidoyl azide (as nitrene source) is developed. The protocol is fast, mild and provides products with a wide range of substrates in 56–86% yields. Additionally, the replacement of aryl amine with alcohol and thiol as nucleophile leads to the formation of sulfonimidoyl isourea and sulfonimidoyl isothiourea respectively, which are not yet reported in the literature. Abstract :